STATUS HOMOCYSTEINE DAN ASAM FOLAT PADA IBU HAMIL MEREKA - Permaesih, Dewi; Rosmalina, Yuniar; Christijani, Reviana; Muhilal, Muhilal (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
HOMOCYSTEINE AND FOLIC ACID STATUS OF ANEMIC PREGNANT WOMEN. Background: Folic acid deficiency among pregnant women in Indonesia is quite prevalent. It is believed to cause the anemia and the risk of infant neutral tube defect. Folic acid plays a certain role in homocysteine convertion into methionine. Serum homocysteine will increase with the decrease folic acid. Objective: To obtain folic acid consumption, homocysteine and folic acid status in pregnant women suffering from anemia using recent method of determination, and relationship of the three variables. Methodology: Pregnant women in the study area were screened by their Hb values under 11 g/dL. Thirty anemic pregnant women consumption was obtained by used 2x24 hours recall method. Folic acid was analysed by Ion Capture Method and homocysteine was analysed by Fluoresence Polarization Immuno assay. Results: Folic acid consumption was 61 ± 50 µg/mL with a range of 3.5 to 15.1 µg/mL. Normal value of serum folic acid was 3.1 to 12.4 µg/mL. Therefore, the value folic acid of pregnant women in this study was still in the range of normal value. Serum homocysteine value in pregnant women was 7.1 ± 1.95 µg/mL with a range of 3.0 to 10.9 µg/mL, while normal value was 5 to 15 µg/dL. Conclusion: homocysteine, folic acid, pregnant women, anemia.